The Impact of Industrial Noise Exposure on Work Stress and Mental Health of Workers: A Study in the Manufacturing Industry - M Ramadhani Firmansyah; Nina Irmayanti Harahap; Diana Chandra Dewi; Susanti Delina (CV. Get Press Indonesia, 2025)
This study examined the relationship between industrial noise exposure, occupational stress, and mental health among manufacturing workers using a quantitative cross-sectional design. From a population of 450 workers, 212 respondents were selected through stratified random sampling. Noise exposure was assessed using a sound level meter with the time-weighted average (TWA) method, while occupational stress and mental health were measured using the Job Stress Scale (JSS) and the General Health Questionnaire (GHQ-12). Data were analyzed descriptively, bivariately with the Chi-Square test, and multivariately with logistic regression. Results showed that most workers were exposed to moderate noise levels (85–90 dB), with 29.2% experiencing high exposure (>90 dB). Moderate stress was reported by 44.3% of respondents, and 25.5% experienced high stress levels. Mental health assessment indicated that 51.9% of workers exhibited mild to moderate–severe psychological distress. Chi-Square analysis demonstrated significant associations between noise exposure and both occupational stress (p = 0.003) and mental health status (p = 0.021). Multivariate findings identified high noise exposure (>90 dB) and prolonged working hours (>8 hours/day) as dominant predictors of increased risk for occupational stress (OR = 2.85) and mental health disorders (OR = 2.34). These results highlight that industrial noise functions not only as an audiological hazard but also as a meaningful psychosocial stressor. The study emphasizes the necessity of integrating noise control strategies, regulation of working hours, and structured stress management interventions into Occupational Safety and Health (OSH) programs to reduce psychological burdens and enhance worker well-being in manufacturing environments.